SARS-CoV-2 infection in patients with autoimmune rheumatic diseases in northeast Italy: A cross-sectional study on 916 patients. Issue 112 (August 2020) - Zen, M.; Fuzzi, E.; Astorri, D.; Saccon, F.; Padoan, R.; Ienna, L.; Cozzi, G.; Depascale, R.; Zanatta, E.; Gasparotto, M.; Benvenuti, F.; Bindoli, S.; et al.
Abstract: Background: Whether patients with autoimmune rheumatic diseases (ARD) have a higher risk for SARS-CoV-2 infection (COVID-19) and how SARS-CoV-2 pandemic impacts on adherence to therapy has not been fully elucidated. We assessed the rate and clinical presentation of COVID-19, and adherence to therapy in a large cohort of patients with ARD followed-up in a tertiary University-Hospital in Northeast Italy. Methods: Between April 9th and April 25th, 2020, after SARS-CoV-2 infection peak, a telephone survey investigating the impact of COVID-19 on patients with systemic lupus erythematosus (SLE), systemic sclerosis (SSc), rheumatoid arthritis (RA), ANCA-associated vasculitis (AAV), and idiopathic inflammatory myopathies (IIM) was administered. Demographics, disease activity status, therapy, occupational exposure, and adherence to social distancing advise were also collected. Results: 916 patients (397 SLE, 182 AAV, 176 SSc, 111 RA, 50 IIM) completed the survey. 148 patients developed at least one symptom compatible with COVID-19 (cough 96, sore throat 64, fever 64, arthromyalgias 59, diarrhea 26, conjunctivitis 18, ageusia/hyposmia, 18). Among the 916 patients, 65 (7.1%) underwent SARS-CoV-2 nasopharyngeal swab (18 symptomatic and 47 asymptomatic), 2 (0.21%) tested positive, a proportion similar to that observed in the general population of the Veneto region. No deaths occurred. 31 patients (3.4%) withdrew ≥1 medication, mainly immunosuppressants or biologics. Adoption of social distancing was observed by 860 patients (93.9%), including 335 (36.6%) who adopted it before official lockdown. Conclusions: COVID-19 incidence seems to be similar in our cohort compared to the general population. Adherence to therapy and to social distancing advise was high. Highlights: SARS-CoV-2 infection rate in ARDs seems to be similar to that of the general population. Adoption of social distancing measures was prevalent among different ARD groups. Earlier social distancing was more common in unremitted patients, treated with multiple drugs. Therapy discontinuation due to COVID-related concerns was rare, but undertaken even by active patients. Therapeutic regimens based on ≥3 drugs were associated with therapy discontinuation in our cohort.